2019
DOI: 10.1002/mame.201800689
|View full text |Cite
|
Sign up to set email alerts
|

Lignin‐Reinforced Ethylene‐Propylene‐Diene Copolymer Elastomer via Hydrogen Bonding Interactions

Abstract: It is still a great challenge to prepare lignin/polyolefin composites with good strength and toughness. Inspired by the energy sacrificial mechanism from biomaterials, dynamic hydrogen bonds (H-bonds) are incorporated into the lignin/ethylene-propylene-diene monomer (EPDM) composite system to improve the interfacial interactions between lignin and EPDM. Such H-bonding interactions are demonstrated to be able to simultaneously improve the modulus, strength, and toughness of lignin/EPDM composites without sacrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Bio‐based materials are non‐toxic, and renewable, which makes them attractive alternatives to formaldehyde‐based adhesives. Various natural bio‐based materials, including tannin, 6 starch, 7 lignin, 8 and protein 9 have been developed and utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Bio‐based materials are non‐toxic, and renewable, which makes them attractive alternatives to formaldehyde‐based adhesives. Various natural bio‐based materials, including tannin, 6 starch, 7 lignin, 8 and protein 9 have been developed and utilized.…”
Section: Introductionmentioning
confidence: 99%
“…[37] DCP has also been successfully used to improve polymer-fiber interactions in highdensity PE-sisal fiber composites, with a typical DCP loading of 1 phr, showing its efficiency during REX of fiber-reinforced composites. [38] In addition, REX has been developed using other compatibilizers, for instance, Mei et al [4] reported that interfacial interactions between lignin and ethylene-propylene-diene monomer (EPDM) could be improved with the use of maleic anhydride grafted PE-octene elastomer (POE-MA) as a reactive compatibilizer. Moreover, they reported the use of 3-amino-1,2,4triazole (ATA) as POE-MA modifier to enhance improved reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2,3 ] Lignin contains a large variety of functional groups, such as hydroxyls groups, carboxyl groups, which can form efficient H‐bounding interactions. [ 4 ] In addition, lignin is considered the main renewable source of aromatic structures. [ 5 ] Different kinds of lignins, called technical lignins, are obtained after the delignification process, such as kraft lignin (KL), soda lignin, and organosolv lignin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 36 ] Moreover, the dynamic vulcanization process can increase the elastomeric viscosity, [ 37,38 ] implying that the process can change the microstructure and morphology of elastomers. Ethylene‐propylene‐diene monomer (EPDM) elastomer is widely used in the PP blends, [ 39 ] and dynamic vulcanization of EPDM leads to an increase of elastic recovery, [ 40 ] a decrease of size, [ 41 ] and a fine dispersion [ 42 ] of EPDM in the PP. Furthermore, smaller agglomerates of polyolefin elastomer (POE) can be obtained after POE is appropriately vulcanized.…”
Section: Introductionmentioning
confidence: 99%